Differences in athletic identity, sport participation, and psychosocial factors following anterior cruciate ligament rehabilitation in youth athletes - McGinley, James; Stapleton, Emily; Gale, Emily; Worrall, Hannah; Podvin, Caroline; Ellis, Henry B.; Wilson, Philip L.; Ulman, Sophia (Frontiers in Psychology, 2024)
Introduction: While youth sports benefit the developing athlete, athletes may also be subject to injury and subsequent return-to-sport protocols. Current return-to-sport criteria emphasize physical measures; however, psychological measures may also be valuable to inform providers of an athlete’s readiness. One such measure is athletic identity, or the degree with which an individual identifies with the athlete role. To better understand athletic identity in return-to-sport, this study aimed to identify relationships and trends between the Athletic Identity Measurement Scale (AIMS), demographic variables, sport participation measures, and the Athletic Coping Skills Inventory-28 (ACSI-28) in youth athletes during rehabilitation following anterior cruciate ligament reconstruction (ACLR). Methods: A retrospective review was completed of patients who underwent ACLR at a sports medicine clinic between October 2019 and May 2021. Patients responded to a series of patient reported outcomes (PROs) regarding physical and psychological function at a pre-surgical baseline and after one year of rehabilitation. Patients were then divided into groups of high/low AIMS and an increased/decreased AIMS between one-year and baseline for comparison. Independent samples t-tests and ANOVAs were run as appropriate with a 95% confidence interval. Results: Eighty-seven patients (15.3 ± 1.8 years; 51.7% female) were included in the final sample. Total AIMS scores decreased from 50.3 to 47.5 over rehabilitation (p=0.019). Furthermore, results indicated that nearly all AIMS scores decreased during rehabilitation, with none showing an increase, but not all domains were significant. Conversely, all sport participation and coping ability PROs increased over the time points except for ACSI-Confidence and Achievement Motivation. Generally, those in the groups with high AIMS and an increase in AIMS also had higher scores in physical function and coping ability PROs, with the groups separated by high/low AIMS exhibiting more frequent statistical significance. Discussion: Given these results, it appears athletes may lose identification with the athlete role after ACLR and struggle even one year into rehabilitation, but those who recover athletic identity best may also be those able to cope most effectively with the stressors induced by injury.